5(a-1)-4(a-2)=2(5a+20)

Simple and best practice solution for 5(a-1)-4(a-2)=2(5a+20) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(a-1)-4(a-2)=2(5a+20) equation:


Simplifying
5(a + -1) + -4(a + -2) = 2(5a + 20)

Reorder the terms:
5(-1 + a) + -4(a + -2) = 2(5a + 20)
(-1 * 5 + a * 5) + -4(a + -2) = 2(5a + 20)
(-5 + 5a) + -4(a + -2) = 2(5a + 20)

Reorder the terms:
-5 + 5a + -4(-2 + a) = 2(5a + 20)
-5 + 5a + (-2 * -4 + a * -4) = 2(5a + 20)
-5 + 5a + (8 + -4a) = 2(5a + 20)

Reorder the terms:
-5 + 8 + 5a + -4a = 2(5a + 20)

Combine like terms: -5 + 8 = 3
3 + 5a + -4a = 2(5a + 20)

Combine like terms: 5a + -4a = 1a
3 + 1a = 2(5a + 20)

Reorder the terms:
3 + 1a = 2(20 + 5a)
3 + 1a = (20 * 2 + 5a * 2)
3 + 1a = (40 + 10a)

Solving
3 + 1a = 40 + 10a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-10a' to each side of the equation.
3 + 1a + -10a = 40 + 10a + -10a

Combine like terms: 1a + -10a = -9a
3 + -9a = 40 + 10a + -10a

Combine like terms: 10a + -10a = 0
3 + -9a = 40 + 0
3 + -9a = 40

Add '-3' to each side of the equation.
3 + -3 + -9a = 40 + -3

Combine like terms: 3 + -3 = 0
0 + -9a = 40 + -3
-9a = 40 + -3

Combine like terms: 40 + -3 = 37
-9a = 37

Divide each side by '-9'.
a = -4.111111111

Simplifying
a = -4.111111111

See similar equations:

| 10=2x-86 | | F(9)=3 | | 1000=r^3/2 | | 3(X+2X)+9R= | | 20y+3x=50 | | ((3y+4)*2)+((y+3)*2)=70 | | .5n+15=3n | | (X+5)(x+5)-49=0 | | -12=w+18 | | 5z-18-z+2= | | 10=(2*6)-8 | | 2x-3x-10=-9 | | B-2b=b+4b+2 | | 3(y-4)= | | 4x+8/4-2=x | | 2x^2-4x/x-2 | | 8+7x+4x=63 | | x+6=x.4 | | 99x+65=-4x | | z(4x^10y^11z^8)= | | 7+3C=-7 | | .25n=2n-21 | | 5(2x-12)+21=2x+21 | | w=4x(y-5) | | 210(-3)= | | 2(3+x)=20+3x | | 9y+2=11y+8 | | z(16xy^3z^3)= | | e^4y-ln(y^2+3)=2x | | Yy-2=y+1y-5 | | 27x^2-54x+2805=0 | | x+8=-2-2+5x |

Equations solver categories